Przyczyny i skutki regionalnego zróżnicowania cen energii elektrycznej w Polsce - Godzisz, Konrad (Reasons and Effects of the Regional Diversification of Electricity prices in Poland, 2008)
The comparison of average prices of electricity supplied to customers in various areas of Poland indicates that the diversification exists. This phenomenon may have an effect on situation of both enterprises and households. The objective of this working paper is to evaluate if existing diversification of electricity prices is justified and may have effect on the situation of energy consumers. It presents the scale of differences in energy costs of supply and its main reasons, i.e. the costs of distribution services which depends on the characteristic of distribution company area, as well as the type of customers. It also includes an attempt to assess the influence of electricity prices diversification on energy consumers. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 305-319